Fault Tolerance and Energy Consumption Scheme of a Wireless Sensor Network - Doo-Soon Park (International Journal of Distributed Sensor Networks)
The commercialization of detection and surveillance systems by sensor networks has recently become more popular in various industries and in ordinary life. Wireless sensor networks (WSNs) may be utilized in areas such as military defense systems, u-care services, and disaster prevention systems. WSNs, which have three primary elements, should be able to communicate through a combination of network and sensor functions. When the size of a sensor network is small, the cost of building it accounts for a large fraction of the total cost. In large-scale sensor networks, however, maintenance costs to replace nodes when they are out of order, and batteries used for wireless communications, greatly increase, in addition to the cost of constructing them. Therefore, measures to detect and respond to sensor faults in a sensor network, as well as a mechanism to predict the energy consumption of sensors, are necessary. Accordingly, this paper proposes a measure to detect and deal with sensors by dividing WSN into fixed WSN and mobile WSN. This paper also suggests a method to predict and express the energy consumption of a sensor network.